Implementasi Model Pentahelix dalam Pengembangan Badan Usaha Milik Desa (BumDes) di Kabupaten Lampung Selatan - Feni Rosalia; Syarief Makhya; Pitojo Budiono (Jurnal Ilmiah Wahana Bhakti Praja, 2023)
The purposes of the writing raised are (1) To describe whether the pentahelix model has been implemented in the management of Village-Owned Enterprises (BumDes) in South Lampung Regency, and (2) To describe the obstacles to implementing the pentahelix model in the management of Village-Owned Enterprises (BumDes) in the Regency South Lampung. The purpose of writing relates to optimizing village development in order to improve the welfare of village communities as stated in Law Number 6 of 2014 concerning Villages. Likewise, in line with the objectives of establishing BumDes, including improving the economy and increasing the income of rural communities. The research method used is through a qualitative approach the researcher makes an objective representation of the symptoms contained in the research problem, namely the implementation of the pentahelix model in the management of BumDes in South Lampung Regency. Data were obtained from interview, observation and documentation techniques. Furthermore, data analysis with data reduction, data presentation and verification/conclusion. The results of the study explained that the implementation of the Pentahelix model has been implemented well in BumDes Management in South Lampung Regency, only in Sidomulto District which has implemented the Pentahelix model in collaboration with 5 stakeholders, namely the Media, Business Community, Academics, and Government as the leading sector. The form of cooperation that is carried out is by holding joint activities where stakeholders are still limited to being facilitators and sponsors of these activities. Therefore, in the future it is hoped that stakeholder collaboration with BumDes can be further enhanced in a more concrete form, namely developing BumDes, increasing the capacity of BumDes resources and efforts to increase BumDes capital.